A Statistical Analysis of System Usability Scale (SUS) Evaluations in Online Learning Platform - Suria, Ozzi (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
This study evaluates the usability of a Moodle-based online learning system at a university using the System Usability Scale (SUS). Introduced in 2019, the platform has been instrumental in facilitating access to educational resources, enhancing the distribution of course materials, and supporting academic activities through interactive features. The SUS was employed to gather subjective feedback from 120 student respondents, providing insights into the system's efficiency, effectiveness, and user satisfaction. Statistical analysis was performed using methods including the Shapiro-Wilk test to address the skewed distribution of the original dataset with a mean SUS score of 71.52 and a high standard deviation of 16.18, indicating varied user experiences. Analysis of sample means was also conducted to achieve a more stable estimate of usability, resulting in a mean of 71.51 with a significantly reduced standard deviation of 2.44, suggesting a more consistent assessment across users. The final SUS score placed the system in the 'C+' category according to the Sauro and Lewis grading scale, indicating that while usability is acceptable, substantial improvements are necessary.